Rediscovering the poorly-known Neotropical katydid Hyperomerus crassipes Redtenbacher, 1891 (Orthoptera: Tettigoniidae: Conocephalinae: Agraeciini): description of male reveals the synonymic status of Uchuca Giglio-Tos, 1898 - Tavares, Gustavo Costa; Nunes-Gutjahr, Ana Lúcia (Zootaxa, 2021)
Hyperomerus Redtenbacher is a genus of Neotropical katydid with only one species, H. crassipes. For more than one hundred years, the only specimen known was the female holotype. Now, more three exemplars were found deposited in the Zoological Collection of the Universidade Federal do Amazonas in Brazil, including the unknown male, which reveals the congeneric status with Uchuca Giglio-Tos species and, consequently, this last genus is being made a junior synonym of Hyperomerus. Additionally, H. crassipes is redescribed, and the records of all species now included within the genus Hyperomerus are updated.